Upaya Meningkatkan Hasil Belajar Matematika melalui Project Based Learning (PjBL) Materi Pengukuran Waktu pada Siswa Kelas I SDN Klampis Ngasem 1 Surabaya - Dwi Nurvita Sari; Wiryanto Wiryanto; Halimatussya’diyah Halimatussya’diyah (Journal on Education, 2023)
In learning certainly can not be separated from the supporting components in teaching and learning activities, one of which is the learning model. This classroom action research was conducted with the aim of implementing a project-based learning model (PjBL) to improve mathematics learning outcomes in the material of measuring time in grade 1 elementary school students. This research was conducted in 3 cycles using a collaborative approach with qualitative and quantitative descriptive methods. The stages in this class action research include planning, action, observation, and reflection. The subjects in this study were 29 students in class 1-D. Research shows that there is an increase in student learning outcomes in Cycles 2 and 3. In the first cycle, only 34% of students succeed in achieving KKM (Minimum Completeness Criteria) scores. Whereas in the second cycle, there was an increase of 55% of students who achieved the KKM score. In cycle 3 the percentage of classical mastery of students' learning outcomes increased to 82.7%. In conclusion, the application of the Project Based Learning (PjBL) learning model can improve the mathematics learning outcomes of class I SDN Klampis Ngasem 1 Surabaya on time measurement material with a fun learning atmosphere with student-centered learning.